Employees Perception of Work-Life Balance Implementation in a Hybrid Work Environment - Ishak, Andi Dorawati; Entong, Andi Ellyanti; Entong, Andi; Haris, Andi Tenri Lawa Putri Lanrang (PT. Maju Malaqbi Makkarana, 2025)
This study examines employees' perceptions of work-life balance implementation in a hybrid work environment, a model that has gained popularity in the post-COVID-19 era. Hybrid work arrangements offer flexibility by allowing employees to alternate between remote and office-based work, providing opportunities to balance professional and personal responsibilities. However, the blurred boundaries between work and personal life in a hybrid setting can create challenges, such as overworking, interruptions during personal time, and social isolation. Using a qualitative approach, this study explores the experiences, challenges, and factors influencing work-life balance in hybrid work environments. Data were collected through semi-structured interviews and focus group discussions with employees from various sectors. The findings reveal that while hybrid work promotes flexibility and autonomy, it also increases the risk of stress and burnout due to a lack of clear boundaries and insufficient organizational support. Factors such as flexible scheduling, supportive leadership, and access to user-friendly digital tools were identified as enablers of work-life balance. This research highlights the dual impact of hybrid work on work-life balance and emphasizes the need for clear organizational policies, leadership training, and technological support to ensure employee well-being. The findings provide actionable recommendations for organizations to optimize hybrid work practices.